2021
DOI: 10.1093/jncics/pkab009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nonmelanoma Skin Cancer in Association With Use of Hydrochlorothiazide-Containing Products in the United States

Abstract: Background European studies reported an increased risk of non-melanoma skin cancer associated with hydrochlorothiazide (HCTZ)-containing products. We examined the risks of basal cell (BCC) and squamous cell carcinoma (SCC) associated with HCTZ compared to angiotensin-converting enzyme inhibitors (ACEIs) in a US population. Methods We conducted a retrospective cohort study in the US Food and Drug Administration’s Sentinel Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 32 publications
4
32
1
Order By: Relevance
“…Eight case-control studies [ 7 , 11 , 13 , 37 40 , 43 ] and four cohort studies [ 10 , 12 , 45 , 46 ] provided risk estimates for hydrochlorothiazide-associated NMSC. The meta-analysis demonstrated increased odds for NMSC among patients receiving hydrochlorothiazide in case-control studies (pooled OR 1.16, 95% CI 1.08–1.24, I 2 = 96%) and cohort studies (pooled HR 1.26, 95% CI 1.04–1.54, I 2 = 100%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight case-control studies [ 7 , 11 , 13 , 37 40 , 43 ] and four cohort studies [ 10 , 12 , 45 , 46 ] provided risk estimates for hydrochlorothiazide-associated NMSC. The meta-analysis demonstrated increased odds for NMSC among patients receiving hydrochlorothiazide in case-control studies (pooled OR 1.16, 95% CI 1.08–1.24, I 2 = 96%) and cohort studies (pooled HR 1.26, 95% CI 1.04–1.54, I 2 = 100%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier systematic reviews have reported that thiazides are associated with an increased risk of skin cancers [ 5 , 8 , 9 ]. In comparison with previous reviews, we included more recent studies, with 13 published from February 2019 to January 2022 [ 10 14 , 36 40 , 43 , 45 , 46 ]. More importantly, our analyses covered a broader range of recent nationwide data, including data from the Brazil, Netherlands, USA, UK, Iceland, Spain, Australia, Taiwan, and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…It is our vision that this becomes the way data quality is shared among networks, with reviewers, and with regulators. The most recent papers published using the PEDSnet, PCORNet, and Sentinel networks [38][39][40] either do not mention how the data used were assessed for quality or they touch on it very briefly. Instead, with a tool like the DQD, a JSON file(s) can be shared as additional material to a publication detailing all data quality checks that were run on the database in which the study was executed.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about HCTZ and sun interactions are well founded. High UV exposure has long been known to increase the risk of severe sunburn and skin cancer [ 9 , 10 ] and, in response to recent evidence from very large observational studies [ 14 , 28 , 29 ], HCTZ labeling in the U.S. now has overt warnings of increased KC risks [ 30 ]. KC is fast becoming a disease (primarily) of the elderly [ 10 , 31 ], likely reflecting accrued exposures to KC risk factors (e.g., sun seeking, ozone depletion) over longer lifetimes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on this topic have been limited by indirect markers of sun exposure such as the self-reported number of lifetime painful sunburns or residential address information indicative of living in sunnier regions. While some studies have adjusted for said markers of sun exposure in their examination of HCTZ use [ 13 , 14 ], analyses of HCTZ effect modification by sun exposure are lacking, with just one known case–control study showing enhanced risk of squamous cell carcinoma among users of photosensitizing medications who also have a tendency to sunburn [ 15 ].…”
Section: Introductionmentioning
confidence: 99%